Recombinant single-chain variable fragment and single domain antibody piezoimmunosensors for detection of HIV1 virion infectivity factor - Ferreira, Guilherme N. M. (2015)
In this paper recombinant single-chain fragments (scFv-4BL), and single domain antibodies (4BL-V-H) and (4BL-VHD) generated against HIV1 virion infectivity factor (Vif) are used to develop piezoinimunosensors for HIV1 recognition. Mixed self assembled mon